Trade and inequality with limited labor mobility: Theory and evidence from China - Muqun Li; Ian Coxhead (Osaka University, Institute of Social and Economic Research (ISER), 2010)
Does globalization increase inequality in developing countries, and if so, how? In a theoretical model of a regionally heterogeneous economy, we show how different regional rates of technical progress due to trade and FDI interact with constraints to unskilled labor mobility. As favored regions benefit more from trade, their growing demand for skills drains skilled workers from disadvantaged areas, and average incomes in the former grow faster than in the latter. Moreover, this unbalanced regional growth may also raise inequality within each region. It could even reduce absolute income per capita in the less favored region. We test these predictions with Chinese data from the Open Door era. Results confirm that different regional growth rates ave increased both interregional and intraregional inequality. Moreover, growth of skills-based export industries in coastal regions is associated, other things equal, with lower incomes for the poor in inland provinces.
Keywords: F16; O15; R1; 330; trade; investment; wage premium; migration; inequality; China; Globalisierung; Soziale Ungleichheit; Binnenwanderung; Regionale Lohnstruktur; China